2007
DOI: 10.1002/jbm.b.30877
|View full text |Cite
|
Sign up to set email alerts
|

Uniform deposition of protein incorporated mineral layer on three‐dimensional porous polymer scaffolds

Abstract: Inorganic-organic hybrid materials designed to facilitate bone tissue regeneration use a calcium phosphate mineral layer to encourage cell adhesion, proliferation, and osteogenic differentiation. Mineral formed on porous materials is often discontinuous through the thickness of the scaffold. This study aimed to uniformly coat the pores of three-dimensional (3D) porous, polymer scaffolds with a bone-like mineral layer in addition to uniformly incorporating a model protein within this mineral layer. A filtration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Moreover, PLGA is most often used in combination other ceramic or polymeric materials that interact with PLGA, thereby enhancing the difficulty to draw unambiguous conclusions on the specific effects of physicochemical characteristics of PLGA on ultimate performance in bone regeneration. In this regard, it is important to notice that relevant information on, for example, polymer molecular weight, [30][31][32][33][34][35] stereochemistry, [31][32][33][34] or end-group functionalization, [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] are often missing, which complicates scientific progress even further.…”
Section: Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, PLGA is most often used in combination other ceramic or polymeric materials that interact with PLGA, thereby enhancing the difficulty to draw unambiguous conclusions on the specific effects of physicochemical characteristics of PLGA on ultimate performance in bone regeneration. In this regard, it is important to notice that relevant information on, for example, polymer molecular weight, [30][31][32][33][34][35] stereochemistry, [31][32][33][34] or end-group functionalization, [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] are often missing, which complicates scientific progress even further.…”
Section: Degradationmentioning
confidence: 99%
“…85 Several studies describe the use of biomimetic processes to produce apatite-coated PLGA constructs for bone tissue engineering by incubation of polymeric scaffolds in simulated body fluid (SBF) to obtain a mineralized scaffold. [32][33][34]86 The resulting coatings were shown to enhance the osteoconductive properties of PLGA. However, this procedure has drawbacks related to the immersion of the PLGA scaffold in SBF, as the scaffold can undergo hydrolytic degradation on soaking in aqueous solutions.…”
Section: Scaffolds Consisting Of Pure Plgamentioning
confidence: 99%
“…14 Although previous studies showed that m-CT may be applicable to monitor in vitro mineralization of porous scaffolds, 19 by m-CT has not been examined. Therefore, to evaluate the accuracy of m-CT data and qualify the amount of mineral, TMC and mineral volume from m-CT data were compared with the amount of calcium in the mineral layers using OCPC method which has been used to characterize biomineral coatings.…”
Section: L-ct For Nondestructive Characterization Of Biomineral Coatingsmentioning
confidence: 99%
“…13,14,16 The existence of biomineral coatings on polymer scaffold surfaces also have been examined using m-CT since polymer is almost radio transparent compared to other radio-dense materials. [17][18][19] However, the 3D volume and distribution of mineral coating within porous scaffolds has not been precisely quantified and verified versus destructive methods. Furthermore, changes in mineral coating following implantation in vivo have not been rigorously quantified in 3D.…”
mentioning
confidence: 99%
“…83 However, the incorporated protein could improve the mineral phase by conveying a function such as improvement of degradation kinetics of the polymer substrate 174,175 or adherence or stimulation of bone forming cells 184,185 (see also above paragraphs on drug delivery in the Peptide Coatings section).…”
Section: Proteins Coprecipitated With Mineralmentioning
confidence: 99%